ETA and state action: the development of Spanish antiterrorism - Ubasart, Gemma (Crime, law and social change, 2019)
On 20 October 2011 ETA announced the ‘definitive cessation of its armed activity’, which had been increasing since shortly after its inception in 1959. On 8 April 2017 it disarmed by handing over its weapons to intermediaries from civil society. On 2 May 2018 ETA announced its dissolution. This was the end of the last ongoing armed conflict in Europe from the wave of political violence - linked to national and class disputes - that swept over the continent starting in the 1960s. This article analyses the development of Spanish antiterrorism in relation to the Basque conflict, observing how a free and democratic Spanish state has responded to the challenge of an armed insurgency that has continued to the present. While the history of the organisation is well known, less so is the development of the reaction to deal with it. ETA’s progression cannot be understood in isolation, but rather needs to be placed into the context of the measures taken by the state, which influenced, shaped, and was shaped by it throughout the course of the conflict.